Effect of leachate recirculation and aeration on volatile fatty acid concentrations in aerobic and anaerobic landfill leachate - Bilgili, M. Sinan; Demir, Ahmet; Varank, Gamze (SAGE PUBLICATIONS LTD, 2012)
The main aim of this study was to investigate the effect of leachate recirculation and aeration on volatile fatty acid (VFA) concentrations in aerobic and anaerobic landfill leachate samples. In this study, two aerobic (A1, A2) and two anaerobic (AN1, AN2) reactors with (A1, AN1) and without (A2, AN2) leachate recirculation were used in order to determine the change of volatile fatty acids components in landfill leachate. VFA degradation rate was almost 100% in each reactor but the degradation rate show notable differences. In aerobic landfill reactors, total VFA concentrations decreased below 1000 mg L-1 after 120 days of operation and only caproic and acetic acids were determined at this time. The stabilization of the VFA concentrations takes about 350 and 450 days for AN1 and AN2 reactors, respectively. VFA concentrations were higher than that of aerobic reactors because of the acidogenic phase occurred in anaerobic environment. According to the results of VFA components, the stabilization of the waste was achieved after 120 days of operation in aerobic landfills. At this time, anaerobic reactors were in the acidogenic phase which results with the high concentrations of VFA. The results also indicated that leachate recirculation does not affect the degradation rate in aerobic landfills as much as it does in anaerobic landfills.
Keywords: Solid waste; aerobic landfill; leachate; volatile fatty acid; gas chromatography; MUNICIPAL SOLID-WASTE; REFUSE DECOMPOSITION; BIOREACTOR LANDFILLS; INHIBITION; DIGESTION; METHANOGENESIS; DEGRADATION; DISPOSAL; SYSTEMS; IMPACT; Engineering; Environmental Sciences & Ecology